Sosialisasi Pembuatan Hand Sanitizer Bebas Alkhol dari Kitosan Kulit Udang di Pesantren Tahfidz Nurul Ilmi Yabis - Karim Kasmudin; Fitria Fitria; Faizal Mahyudin (Jurnal Pengabdian Ahmad Yani, 2022)
Corona virus disease (Covid-19) is a disease caused by a virus that attacks the respiratory tract and still continues today. The death toll from Covid-19 continues to rise in Indonesia as the number of positive cases of the coronavirus reaches thousands of people. One of the bacterial infections that cause respiratory infections is Klebsiella pneumoniae. One of the preventive efforts to prevent the spread of infections caused by the corona virus and bacteria is the renewal of waterless hand sanitizers called antiseptic hand sanitizers or hand sanitizers. The approach method used is to provide understanding to the students about the potential of waste treatment in the city of Bontang. Continue by socializing the manufacture of chitosan from shrimp shells and the process of processing chitosan to produce hand sanitizers. From the results of this training, it can be concluded with enthusiasm from the students that the activities are carried out well and are able to increase students' knowledge about the potential of waste in the surrounding environment and it is hoped that they will be able to practice making hand santizers on a simple scale. Keywords: Chitosan, Hand Santizer, Alcohol-Free, Islamic Boarding School Students.